Micro-analysis Tanah Ekspansif yang Diperbaiki Secara Kimiawi - Anita Setyowati Srie Gunarti; Fajar Prihesnanto (Borneo Engineering : Jurnal Teknik Sipil, 2023)
Road construction on expansive soil faces many problems such as deflection, longitudinal cracks, circular cracks and spreading cracks in road construction due to the large nature of swelling and shrinkage. This study aims to identify changes in the mineralogy microstructure and chemical properties of the soil in chemically corrected expansive soils so that solutions for expansive soil improvement are obtained by utilizing local materials based on industrial waste, namely Fly ash and Waste Foundry Sand. The research method is in the form of laboratory experiments, namely Structure Electron Microscope and XRD tests on native soil and soil stabilized with Fly ash and Waste Foundry Sand to analyze mineral structure and chemical changes. The results of the analysis found that the effect of the two types of additives on expansive soils was descriptively significant. The addition of fly ash and WFS to the soil makes the pores and cracks filled with fly ash particles and some form of hydration. After the addition of Fly ash and WFS, ion exchange and pozzolanic reactions from fly ash occur to make the flake and flocculant structure of the soil cement into a crystal or block structure, thereby increasing the compactness and integrity of the soil sample.